Sales Management dalam Pengukuran Key Performance Indicator Dengan Menggunakan Metode C4.5 pada CV.X - Feronica Natalia Rivaldi; Silvia Rostianingsih; Yulia Yulia (Jurnal Infra, 2022)
CV.X is a wholesaler company that sells daily necessities. CV.X holds thousands of brands for the types of products sold. Currently, the company has a system that is still limited to desktop applications so that data is still processed manually before being entered into desktop applications. This can cause non-optimal performance in maximizing each salesperson as well as the human error factor that appears. In addition, the company also needs a system that can organize existing business processes, especially the sales side. The company also limited in terms of available reports and from the absence of an evaluation platform to analyze the performance of Key Performance Indicators from working salespersons. This causes the company to have no feedback to find out the measurements on the salesperson that affect its sales. The sales management system is made using a website base using the Codeigniter framework and a mobile application using the Flutter framework. This application can manage business processes related to sales more integrated. The C4.5 method is also used to overcome the grouping of available attributes. With this method, it helps to analyze the attributes with the greatest influence in influencing the achievement of performance in the salesperson. The end result of this program is the integration of business processes, especially sales, such as placing orders, shipping, submitting returns, sending and receiving returns and other processes. Users can also access existing reports in the form of table data and graphic data.